Novel mouthpiece for reducing the gag reflex during esophagogastroduodenoscopy. Issue 4 (2nd October 2019) - Fujiwara, Kazunori; Matsumoto, Kazuya; Ueda, Naoki; Ueki, Masaru; Fukuhara, Takahiro; Ikebuchi, Yuichiro; Isomoto, Hajime; Takeuchi, Hiromi
Abstract : Background and Aim: Discomfort associated with the gag reflex during transoral endoscopy can be troublesome. To overcome this problem during esophagogastroduodenoscopy (EGD), we recently developed a novel mouthpiece. The aim of the present study was to compare acceptance and tolerability of transoral EGD with conventional and new mouthpieces in unsedated patients and analyze the effects of the new mouthpiece. Methods: This study consisted of two phases of cephalometric and EGD examinations to analyze the effects of the new mouthpiece. Cephalometry was carried out in six subjects to evaluate differences in the size of the pharynx (anteroposterior diameter of the oropharynx and longitudinal diameter of the oral cavity) when subjects held the conventional mouthpiece (MAJ674) or the new mouthpiece in their mouths. EGD was done in 10 subjects using the conventional or new mouthpiece to evaluate the number of times the gag reflex occurred, examinee discomfort, and endoscope operability during EGD using a visual analogue scale (VAS). Results: Anteroposterior diameter of the oropharynx and longitudinal diameter of the oral cavity were significantly larger with the new mouthpiece than with the conventional mouthpiece (oropharynx: P  = 0.03; oral cavity: P  =   0.03). With the new mouthpiece during EGD, subjects had significantly fewer instances of the gag reflex ( P  =   0.01); VAS score for discomfort was significantly lower ( P  <   0.01) and score for endoscope operability was significantly higher ( P  =   0.04). Conclusion: The new mouthpiece we developed reduced the gag reflex during EGD by extending the pharynx, thus decreasing examinee discomfort and increasing endoscopic operability.